Spirituality and self-management in coronary heart diseases patient - Fikriana, Riza; Afik, Al; Aditya, Ronal Surya (Intelektual Pustaka Media Utama, 2025)
Coronary heart disease is still the leading cause of death globally. The purpose of this study was to analyze the effect of spirituality on the self-management of coronary heart disease patients. The research design used a cross-sectional study. Samples were 145 patients who had been diagnosed with coronary heart. The research variables are spirituality and self-management. The instrument uses a questionnaire. Data analysis was performed by linear regression test. The results of the study show that the spirituality of coronary heart disease (CHD) patients on the belief in God dimension is 51% high, search for meaning is 74.5% high, mindfulness is 66.2% high and feeling of security is 59.3% high. Meanwhile, the self-management of problem recognition 52.4% good, outcome of expectancy 62.8% good, planning 50.3% good and decision making 94.5% good. The results of the linear regression analysis test showed that belief in God had an effect on problem recognition (p-value 0.004), outcome expectancy (p-value<0.001) and planning (p-value<0.001). While search for meaning, mindfulness and feeling of security do not affect all indicators of self-management.